# Derivative question

I need to find the derivative of:

$$h(x) = \int_{0}^{x^2} (1-t^2)^{1/3} \, dt$$

Would the answer to that just be:

$$(1-x^4)^{1/3}?$$

-
$h(x) = g(x^2)$ where $g(x) = \int_0^x (1 - t^2)^{1/3} \, dt$. What you've written down is $g'(x^2)$, which is not the same as $h'(x)$. Use the chain rule. – Qiaochu Yuan May 16 '11 at 20:56
– Isaac May 16 '11 at 22:53

## 2 Answers

Let $v = x^2$ then $$\frac{\mathrm{d}}{\mathrm{d}v} \int_0^{v} f(t) \mathrm{d}t = f(v)$$ so $$\frac{\mathrm{d}}{\mathrm{d}x} \int_0^{x^2} f(t) \mathrm{d}t = \frac{\mathrm{d}v}{\mathrm{d}x} \frac{\mathrm{d}}{\mathrm{d}v} \int_0^{v} f(t) \mathrm{d}t = 2x f(x^2).$$

-

If $F(x)=\int_{a}^{x}f(t)\;\mathrm{d}t$, then $F^{\prime }(x)=f(x)$. By the chain rule if $F(x)=\int_{a}^{u(x)}f(t)\;\mathrm{d}t$, then

$$F^{\prime }(x)=F^{\prime }(u)u^{\prime }(x)=f(u(x))u^{\prime }(x).$$

In the present case $F(x)=h(x)$, $u(x)=x^{2}$ and $f(t)=(1-t^{2})^{1/3}$. Hence $u^{\prime }(x)=2x$ and $f(u(x))=f(x^{2})=(1-x^{4})^{1/3}$.

Thus

$$h^{\prime }(x)=2(1-x^{4})^{1/3}x.$$

A generalization is to find the derivative of an integral where both limits are functions of $x$, as in this question.

-